KEPUASAN KONSUMEN TERHADAP CAKE DI L’CHEESE FACTORY PEKANBARU - Rahmawati, Dianty; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aim to know the customer satisfaction on the cake, and to know customer satisfaction in the price. This research is a quantitative research. As for the population of this research is consumer eat and drink in L’Cheese Factory, sample of this study totalling 100 person. Based on the research was conducted, can improve customer satisfaction on the cake so as to increase the benefit of sales.Keywords : Costumer Satisfaction, Cake.